Сучасні підходи до викладання фізики - Апуневич, Софія (Видавництво Львівської політехніки, 2012)
Анализируются современные подходы к преподаванию физики в высшем учебном заведении на примере кафедры физики и математики Львовского национального университета ветеринарной медициныи биотехнологий имени С. Гжицкого. Преподавание физики ориентировано на формирование студента как специалиста, способного самостоятельно ставить перед собой задачу, планировать этапы ее решения и добиваться положительного результата. The article analyses modern approaches to physics teaching in higher educational institution on the example of physics and mathematics department of S. Z. Gzhytskyj National University of Veterinary Medicine and Biotechnologies of Lviv. Teaching physics is aimed at the formation of a student as a specialist which can independently set a problem, plan step-by-step its solution and achieve positive results.
Современные подходы к преподаванию физики
Modern approaches to physics teaching
Keywords: физика; эксперимент; теория конструктивизма; образование; physics; experiment; theory of constructivism; education